Anisotropic carbon nanotube for new type of angle sensor development - Saleh, Tanveer; Abdul Muthalif, Asan Gani (2016)
Vertically Aligned Carbon Nanotubes (VACNTs) has captured attention by the researchers because of their flexibility and other attractive engineering properties. They are promising to be used as a functional bulk material in MEMS as well [1]. VACNT array (CNT forest) is known to be the darkest material on Earth because of their unique absorption index. However, this author has shown and explained that tip bent carbon nanotube forest can reflect light like mirror [2].This paper reports that selectively tip bent CNT forest act as an anisotropic mirror, and this property can be exploited to fabricate CNT-based flexible angle sensor that is first of its kind. In this report, we presented a method that can bend the tips of the CNT inside a VACNT array as described in Fig. 1(a). A rigid cylindrical tool rolls over the CNT forest to bend and align the CNTs in the direction of the tool motion. The alignment of the CNTs after process can be observed in Fig. 1(b). Later optical characterization was carried out (on the bent CNT zone) using a polarized laser source as explained in Fig. 1(c). It was observed that if we rotate the sample from 0 to 90 degree, the reflectance is decreasing; this is because the polarization reflection changes from along the nanotube to the perpendicular direction of the nanotubes which is also supported by the findings of Deheer et.al [3]. The result of this analysis is shown in Fig. 1(d). It can be seen that from 10-90 degree the graph is quite linear and the hysteresis of the curve is minimal. The average sensitivity was found to be 0.155%/degree rotation. This finding opens the gateway to fabricate a new CNT-based flexible and miniaturize angle sensor.....